2021
DOI: 10.3389/fimmu.2021.761354
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Glial Fibrillary Acidic Protein Astrocytopathy in Children: A Retrospective Analysis of 35 Cases

Abstract: ObjectiveTo analyze the clinical manifestations, imaging, electroencephalography, treatment, and prognosis of 35 cases of autoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A) in children.MethodsChildren hospitalized in the Department of Neurology, Hunan Children’s Hospital, China, between January 2015 and June 2021, owing to autoimmune diseases of the central nervous system were subjected to a cell-based assay (CBA). The assay identified 40 children positive for GFAP-immunoglobulin (Ig)G antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 15 publications
1
25
1
Order By: Relevance
“…Antibody (GAD65 and hu)-mediated AE seizures are often poorly responsive to ASMs alone ( 50 ) and only moderately responsive to immunotherapy supplemented with ASMs, narcotics plus a ketogenic diet, or tumor therapy. In anti-GFAP AE with seizures, immunotherapy supplemented with ASMs may provide a good prognosis ( 51 , 52 ). Due to the good responses to treatment both were administered to children ( 51 ); however, these data are not comparable.…”
Section: Resultsmentioning
confidence: 99%
“…Antibody (GAD65 and hu)-mediated AE seizures are often poorly responsive to ASMs alone ( 50 ) and only moderately responsive to immunotherapy supplemented with ASMs, narcotics plus a ketogenic diet, or tumor therapy. In anti-GFAP AE with seizures, immunotherapy supplemented with ASMs may provide a good prognosis ( 51 , 52 ). Due to the good responses to treatment both were administered to children ( 51 ); however, these data are not comparable.…”
Section: Resultsmentioning
confidence: 99%
“… 68 , 75 Given the overall rarity of double positive cases based on the results of the larger studies, and considering the superior specificity of the AQP4-IgG test compared to the MOG-IgG test, and that a reliable cell-based-assay (CBA) for detecting MOG-IgG has been available just recently (2017), there is a high possibility that most of the double positive cases may likely be AQP4-IgG + NMOSD with false positive MOG-IgG test results, especially in reports made before this time with using enzyme-linked immunosorbent assay (ELISA). 68 , 75 …”
Section: Discussionmentioning
confidence: 99%
“…MOGAD was perceived primarily as a monophasic CNS inflammatory disease, but further observations showed that a relapsing course occur in 28–60% of patients, and in up to 83% of cases with long-term observation, especially those with persistent positive MOG-IgG status. 99,143 Some evidence of subclinical disease activity and progression has been shown to be present in some of the patients with MOGAD. 2 Patients with anti-NMDAR-EN tend to have more severe neurologic presentations, and poor long-term functional outcomes, and the mortality rate has been reported between 5% and 7%.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of GFAP-A should be based on the clinical symptoms, imaging, EEG characteristics, and treatment response. GFAP antibody is positive in the serum of some patients before positive detection in CSF, which may be due to the occurrence of peripheral nerve injury earlier than injury in the central nervous system [ 9 ]. In this case, the patient started with fever, headache, and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 35 children with GFAP-A reported by Fang et al, 11 (31.4%) were positive for other antibodies, and one patient developed autoimmune GFAP-A 1 year after the diagnosis of AQP4 antibody-associated neuromyelitis optica (NMO). One MOGAD patient was found to be positive for antibodies to GFAP several months after treatment [ 9 ]. Of the 30 GFAP IgG-positive patients reported by Yang et al, 10 had overlap syndrome, with one patient developing GFAP-A 10 years after diagnosis of NMO and the other diagnosed GFAP-A 1 year after diagnosis of anti-NMDAR encephalitis [ 10 ], similar to this patient.…”
Section: Discussionmentioning
confidence: 99%